A rare case report of uterine carcinosarcoma with bilateral ovarian Brenner tumors - Wan, Xinyao; Bi, Fangfang; Xin, Bing; Qiao, Chong (Frontiers in Oncology, 2025)
BackgroundUterine carcinosarcoma is a rare, highly aggressive malignancy characterized by both carcinomatous and sarcomatous components. Brenner tumors of the ovary are uncommon epithelial neoplasms, usually benign but occasionally coexisting with other pathologies. The co-occurrence of these two entities is extremely rare and poses diagnostic and therapeutic challenges.MethodsWe report a case of a 58-year-old female presenting with scant yellowish vaginal discharge. Imaging studies revealed an intrauterine mass. Histopathological analysis of curettage specimens confirmed endometrial malignancy. The patient underwent radical surgical resection followed by histopathological and immunohistochemical analysis.ResultsHistopathology confirmed uterine carcinosarcoma comprising high-grade endometrial adenocarcinoma and pleomorphic sarcoma with chondrosarcoma differentiation. Bilateral ovarian Brenner tumors were also identified. Given the aggressive nature of carcinosarcoma, the patient was referred for adjuvant therapy.ConclusionThis case highlights the importance of prompt pathological evaluation in atypical gynecologic presentations. Early diagnosis through histopathology and immunohistochemistry is crucial for managing rare and aggressive tumors such as uterine carcinosarcoma, particularly when coexisting with other uncommon neoplasms like Brenner tumors. Multidisciplinary care and individualized treatment plans are essential for optimizing outcomes.